using two stay two stray technique in teaching reading comprehension at junior high school - Titi Mulya; Yetti Zainil (Universitas Negeri Padang, 2019)
ABSTRACTMulya, Titi. 2019. Using Two Stay Two Stray Technique in Teaching Reading Comprehension for Junior High School Students This paper discusses how to use Two Stay Two Stray technique in improving students reading comprehension for junior high school. Based on writer’s experience, many students have difficulties in reading such as lack of vocabulary, lack of motivation and they are sometime not interested in reading text. Considering these problems, teacher needs to apply a technique in teaching and learning process to help the students understand the text. Two Stay Two Stray technique is conducted by group discussion. Every group consist of four students. Two students will stay at group and two other will leave the group and become guest in the next group. The group discuss the course material with their friends for the text group would also exchange members for a while in order to share mutual discussion. The function of this technique is to allow the students to visualize the important component of narrative text, including identification and description. By applying the Two Stay Two Stray technique in reading descriptive text, the teacher can reach the goal of teaching descriptive text in reading comprehension to junior high school students. Keywords: Reading, Descriptive Text, Two Stay Two Stray technique.